Strategic planning in civil engineering companies in Maranhão: Analysis of the main methodologies used (Research, Society and Development, 2021)
Due to changes in the economic scenario, growth and moments of financial crisis, there were major changes in company management, that is, competitiveness was accentuated and the market became more discerning, demanding more innovative, efficient companies , effective and versatile. Therefore, this research aims to conduct a study on the main strategic planning methodologies used by civil engineering companies in the state of Maranhão, as well as in their enterprises. To carry out this study, a literature review on strategic planning was prepared and a questionnaire was created and applied in some civil engineering companies in the state. It was observed that all the companies interviewed carry out strategic planning with the participation of qualified and experienced employees, and also review the methods at least once a month, in addition to disseminating the decisions taken to the most diverse sectors of the company. Furthermore, it was possible to conclude that each company has its own strategic planning methods.